Potential Risks and Spatial Variation of Heavy Metals in Water and Surface Sediment of Pattani Bay, Thailand - Kanjana Imsilp; Pattanasuda Sirinupong; Pun Yeesin; Wachiryah Thong-asa; Phanwimol Tanhan (Toxics)
This investigation examined the physicochemical characteristics and heavy metal contamination within the surface sediments and aquatic environments of Pattani Bay, Thailand, throughout both wet and dry seasons. The sediments were primarily composed of fine-grained materials, specifically silt and clay, and exhibited greater propensity to absorb heavy metals from water. Notably elevated concentrations of Cd and Pb were detected, particularly within riverine sediment deposits. This indicates that riverine inputs are significant pathways of the contamination and potentially associated with historical mining activities. Seasonal fluctuations affected physicochemical parameters as well as metal concentrations. The heightened levels of Cd and Pb during the wet season were attributed to runoff phenomena. Pollution indices including the Contamination Factor (CF), pollution load index (PLI), and geoaccumulation index (Igeo) demonstrated moderate to extremely high contamination levels of Cd and Pb in certain areas. The Principal Component Analysis (PCA) suggested possible similar sources for multiple metals including Cd, Cu, Pb, and Zn. The results showed that the heavy metal pollution present is serious, especially for Cd and Pb. These could lead to high ecological health risks and so it is necessary to focus on implementing environmental management strategies for Pattani Bay.